Household welfare impacts of an agricultural innovation platform in Uganda. (8th July 2020) - Ahimbisibwe, Beine Peter; Morton, John F.; Feleke, Shiferaw; Alene, Arega; Abdoulaye, Tahirou; Wellard, Kate; Mungatana, Eric; Bua, Anton; Asfaw, Solomon; Manyong, Victor
Abstract: Technical approaches to food production are important to the food security of growing populations in developing countries. However, strategic investments in research and farm‐level adoption require greater coherence in agricultural, societal, and local policies. The Agricultural Innovation System (AIS) and formation of the Cassava Innovation Platform (CIP) in Uganda were designed to stimulate interactions between researchers and farmers, leading to the development of improved cassava varieties through participatory plant breeding (PPB) and participatory variety selection (PVS). Moreover, the establishment of a community‐based commercialized seed system called Cassava Seed Entrepreneurship (CSE) has made an important contribution to the rapid multiplication and dissemination of clean planting materials in Uganda. The impact of CIP participation on rural household welfare was measured by household consumption expenditure per capita. The Endogenous Switching Regression (ESR) model was applied to data from a formal household survey conducted in the eastern, northern, and mid‐western regions of Uganda. The education, farm size, livestock size, access to credit, cost of cassava planting materials, access to extension service, access to training, and social group membership are significantly associated with CIP participation. CIP participation resulted in a 47.4% increase in household consumption expenditure. This important evidence highlights the need to promote agricultural innovation platform for improving rural livelihoods. Moreover, CIP participation has impact heterogeneity within the participant group that is conditional on household characteristics such as the gender of the household head, pointing to the need to tailor specific interventions and target specific groups within farm households. Abstract : The study has sought to test whether farmers' participation in agricultural innovation platform has led to improved rural livelihoods in Uganda.